2013
DOI: 10.7224/1537-2073.2012-021
|View full text |Cite
|
Sign up to set email alerts
|

Attributional Style and Depression in Multiple Sclerosis

Abstract: Several etiologic theories have been proposed to explain depression in the general population. Studying these models and modifying them for use in the multiple sclerosis (MS) population may allow us to better understand depression in MS. According to the reformulated learned helplessness (LH) theory, individuals who attribute negative events to internal, stable, and global causes are more vulnerable to depression. This study differentiated attributional style that was or was not related to MS in 52 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…On a conceptual level, our results from the CFA extend the findings from a recent report that neurovegetative symptoms are poor indicators of depression in MS. 32 Moreover, our findings are in line with an empirical exploration of attributional style and learned helplessness in MS-depression, where MS patients more likely listed non-MS-related than MS-related causes of negative events. 33 Our results now integrate such findings into a larger conceptual framework to indicate that while vegetative symptoms are frequently correlated with depression, they have little impact on the underlying construct of depression, which is indistinguishable in depressed patients with or without a neurological disorder such as MS.…”
Section: Discussionmentioning
confidence: 56%
“…On a conceptual level, our results from the CFA extend the findings from a recent report that neurovegetative symptoms are poor indicators of depression in MS. 32 Moreover, our findings are in line with an empirical exploration of attributional style and learned helplessness in MS-depression, where MS patients more likely listed non-MS-related than MS-related causes of negative events. 33 Our results now integrate such findings into a larger conceptual framework to indicate that while vegetative symptoms are frequently correlated with depression, they have little impact on the underlying construct of depression, which is indistinguishable in depressed patients with or without a neurological disorder such as MS.…”
Section: Discussionmentioning
confidence: 56%
“…On this account, the reformulated theory of learned helplessness would appear particularly applicable to people with this condition. Two studies [ 5 , 6 ] have considered the application of this theory of depression [ 4 ] to people with MS, demonstrating that stress interacts with attributional style to explain significant depressive symptoms. Kneebone and Dunmore [ 5 ] found global attributional style which interacted with negative events including life stressors and the time since last symptom exacerbation, to explain significant amounts of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Kneebone and Dunmore [ 5 ] found global attributional style which interacted with negative events including life stressors and the time since last symptom exacerbation, to explain significant amounts of depression. More recently, another study found that stress, operationalised as daily hassles, mediated the relationship between attributional style and depression [ 6 ]. Unfortunately, a major limitation with these studies is that the support for the relationship has only been based on cross-sectional data.…”
Section: Introductionmentioning
confidence: 99%